2015
DOI: 10.1016/j.gca.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between l-aspartate and the brucite [Mg(OH)2]–water interface

Abstract: The interaction of biomolecules at the mineral-water interface could have played a prominent role in the emergence of more complex organic species in life's origins. Serpentinite-hosted hydrothermal vents may have acted as a suitable environment for this process to occur, although little is known about biomolecule-mineral interactions in this system. We used batch adsorption experiments and surface complexation modeling to study the interaction of L-aspartate onto a thermodynamically stable product of serpenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 71 publications
0
32
1
Order By: Relevance
“…The authors attributed the increase in adsorption to the formation of a cation–ligand complex, where the M 2+ cation acted as a bridge between the clay surface and the nucleic acid. Similarly, our previous investigations of brucite [Mg­(OH) 2 ] revealed that the surface adsorption of aspartate and ribose was enhanced in the presence of Ca 2+ . , We used a surface complexation model to predict that a cooperative calcium–aspartate complex adsorbs at the brucite–water interface via a “cation-bridge” configuration …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors attributed the increase in adsorption to the formation of a cation–ligand complex, where the M 2+ cation acted as a bridge between the clay surface and the nucleic acid. Similarly, our previous investigations of brucite [Mg­(OH) 2 ] revealed that the surface adsorption of aspartate and ribose was enhanced in the presence of Ca 2+ . , We used a surface complexation model to predict that a cooperative calcium–aspartate complex adsorbs at the brucite–water interface via a “cation-bridge” configuration …”
Section: Introductionmentioning
confidence: 89%
“…In this study, we tested this prediction by investigating the adsorption of aqueous solutions of the five amino acids aspartate, glycine, lysine, leucine, and phenylalanine in equimolar mixtures in the presence of brucite with and without CaCl 2 . These five amino acids were chosen because they have a wide range of pI values (between 2.98 and 9.74) relative to the estimated PZC of brucite of 10.5 . Furthermore, we tested the accuracy of the calculations made by the previously established surface complexation model by making electrophoretic mobility measurements of the brucite surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of molecular adsorption/desorption reactions on mineral surfaces, while not directly measuring TOFs, also shed light on these reaction rates. For example, we find that amino acids, sugars and nucleosides exposed to rutile (TiO 2 ), brucite (Mg(OH) 2 ) or clay minerals typically approach equilibrium concentrations in 1-6 h [78,[101][102][103]-values that imply turnover rates less than 10 3 s per active site. Accordingly, we suggest a plausible average time, t, for prebiotic organic reactions on mineral surfaces: t = 10 3 s/reaction.…”
Section: (B) Estimation Of Prebiotic Chemical Reactions On Earthmentioning
confidence: 97%
“…Pyr Pyrrhotite, troilite, arsenopyrite, pyrite, marcasite, sphalerite, chalcopyrite Novikov and Copley (2013). Estrada et al . (2015).…”
Section: Concentrationmentioning
confidence: 99%